Physics, Philosophy and Psychoanalysis
XVIII, 339 p.
Keywords: To celebrate Adolf Griinbaum's sixtieth birthday by offering him this bouquet of essays written for this purpose was the happy task of an autonomous Editorial Committee: Wesley C. Salmon, Nicholas Rescher, Larry Laudan, Carl G. Hempel, and Robert S. Cohen. To present the book within the Boston Studies in the Philosophy of Science was altogether fitting and natural, for Griinbaum has' been friend and supporter of philosophy of science at Boston University for twenty-five years, and unofficial godfather to the Boston Colloquium. To regret that we could not include contributions from all his well-wishers, critical admirers and admiring critics, is only to regret that we did not have an encyclopedic space at the committee's disposal. But we, and all involved in this book, speak for all the others in the philo sophical, scientific, and personal worlds of Adolf Griinbaum in greeting him on May 15, 1983, with our wishes for his health, his scholarship, his happiness. Our gratitude is due to Carolyn Fawcett for her care and accuracy in editing this book, and for the preparation of the Index; and to Elizabeth McMunn for her help again and again, especially in preparation of the Bibliography of the Published Writings of Adolf Griinbaum; and to Thelma Griinbaum for encouraging, planning, and cheering. Boston University R.S.C. Center for the Philosophy and History of Science M.W.W.